Pengaruh Latihan Zig-Zag Run Terhadap Kecepatan Tendangan Samping (T) Pada Siswa Ekstrakurikuler Pencak Silat di SMA Negeri 1 Sukagumiwang Kabupaten Indramayu - Warjono, Warjono; Fahrudin, Fahrudin; Sumarno, Ardawi (Peneliti.net, 2023)
This study aims to determine the effect of the zig-zag run training method on side kick speed (T) in martial arts extracurricular students at SMA Negeri 1 Sukagumiwang, Indramayu Regency. This research uses quantitative methods. The population in this study were 20 students. This study used a total sampling technique, because researchers took the entire population. Data processing was carried out using SPSS Software Version 25. Instrument analysis carried out was Validity and reliability. While the data analysis technique used is normality test, homogeneity and hypothesis testing which consists of Chi-square analysis, Levene test and t-test using the independent t-test. Based on the normality test, it can be seen if the data is normal because Sig. > 0.05, that is, in the pretest control group, a score of Lo = 0.566 was obtained, then the post-test results obtained a score of Lo = 0.854. Levene test is obtained if Sig. > 0.05, namely the value of Sig. 383 > 0.05 which indicates that the data is homogeneous. The independent t-test is obtained if the sig. (2-tailed) < 0.05, namely the sig. (2-tailed) = 0.004 less than the significance level (a) = 0.05, H0 is rejected and H1 is accepted, meaning there is an influence. The conclusion in this study is that there is an effect of the zig-zag run training method on the speed of side kicks (T) in pencak silat extracurricular students at SMA Negeri 1 Sukagumiwang, Indramayu Regency.